Consumer Preferences On Coffee Shop Attributes - Wachdijono, Wachdijono; Hudaya, Andung Rokhmat; Wilastriani, Irma (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
Today, many coffee shop businesses are growing, including in Cirebon. For this reason, coffee shop business actors strive to be an option for consumers based on their preferences. This study aims to determine the attributes with the level of coffee shop attributes and the attributes that coffee shop consumers most like. The study was conducted in Cirebon City from January to July 2020. The research design is descriptive with survey methods. The number of samples was 100 respondents, and the sampling technique is incidental. Data analysis using conjoint. The results showed the attributes and levels of coffee shop attributes that became consumer preferences: 1) attributes of brewing methods with espresso-based coffee levels, 2) price attributes with a level of Rp. 15,000.00 to Rp. 20,000.00 3) promotional attributes with prize levels, 4) advertising attributes with electronic media levels, 5) location attributes with levels close to the main road, 6) facility attributes with parking area levels, 7) service attributes with service speed levels, and 8) payment system attributes with cash payment levels. The attribute that coffee shop consumers like the most is the price attribute. Therefore, it is recommended that coffee shop business actors in Cirebon City always pay attention to the current prices by setting a reasonable price, not too high but also not too low. However, coffee shop business actors still have to make wise efforts, namely setting prices that always consider operational costs, such as raw materials, labor, space rent, and other factors involved in coffee shop operations.